1996
DOI: 10.1152/jappl.1996.80.3.1006
|View full text |Cite
|
Sign up to set email alerts
|

Presence of WBC, decreased strength, and delayed soreness in muscle after eccentric exercise

Abstract: The purposes of this study were to assess the presence of 99mTc-labeled white blood cells (WBC) in exercised muscle compared with nonexercised muscle over time and to determine the time course of delayed onset muscle soreness (DOMS) and eccentric torque in 10 female subjects. A pretest was followed by 300 eccentric repetitions of the right quadriceps. DOMS and eccentric torque were measured at 2, 4, 20, 24, 48, and 72 h postexercise. Eccentric torque was also tested at 0 h. Radionuclide images of both quadrice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
136
5
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(167 citation statements)
references
References 0 publications
22
136
5
4
Order By: Relevance
“…The acute reduction in force-generating capacity of 47±5% is in line with earlier observations using the same exercise protocol (23). However, in our subjects a rather large variation in force deficit was observed, ranging from 19 to 73%.…”
Section: Paragraph 32supporting
confidence: 93%
“…The acute reduction in force-generating capacity of 47±5% is in line with earlier observations using the same exercise protocol (23). However, in our subjects a rather large variation in force deficit was observed, ranging from 19 to 73%.…”
Section: Paragraph 32supporting
confidence: 93%
“…In noninjured controls, P o was 8.24 Ϯ 1.34 N, and within 15 min after the eccentric contraction, maximal tetanic tension decreased to 4.23 Ϯ 0.22 N. Tetanic tension continued to decrease (2.83 Ϯ 1.03 N at day 3). This further decline in muscle force has been noted in other studies and has been termed a "secondary injury" (21), likely due to inflammation (34,35,46,51,57). Standard histological staining (hematoxylin and eosin) of sections 1 day after the eccentric contraction showed signs of a robust response, with numerous cells migrating from the vasculature into the extracellular space (data not shown), indicative of an inflammatory response.…”
Section: Muscle Contractile Function and Membrane Damagesupporting
confidence: 70%
“…These data are in agreement with others who have demonstrated a 53% decrease in elbow flexors after 100 repeated eccentric actions (Linnamo, Bottas, & Komi, 2000) and repeated actions of the knee extensors (Brown, Child, Day, & Donnelly, 1997;MacIntyre, Reid, Lyster, Szasz, & McKenzie, 1996). However, others have shown that repeated eccentric muscle actions are extremely fatigue resistant despite high force production (Emery et al, 1994;Hortobagyi et al, 1996;Tesch, 1990 It has been suggested that an ICC of 0.88 or above and CV not exceeding ± 6% demonstrates good reliability in isokinetic strength testing (Gleeson & Mercer, 1996).…”
Section: Discussionsupporting
confidence: 93%